Symbolic Meanings in the Social Interaction of Santri in the Pesantren Environment - Firmansyah; Irja Putra Pratama; Munir (Al-Hayat: Journal of Islamic Education, 2024)
This study examines the symbolic meaning of students' social interactions with ustadz, teachers, fellow students, and parents at the Muhammadiyah Boarding School Al-Manar South Sumatra. Using a descriptive qualitative approach based on case studies, this study used observation, interviews, and documentation as data collection techniques. Analysis techniques included coding and categorizing the collected data to identify related patterns and themes. This study's findings revealed that students' interactions with ustadz and teachers are symbolized by bowing and kissing the hand, reflecting respect, religious obedience, and social hierarchy. These traditions strengthen the cultural and spiritual bonds between students and their teachers. Among fellow students, calling each other akhi (brother) and ukhti (sister) symbolizes respect, unity, and leadership development. These interactions help strengthen social structures and foster character development. Interactions with parents expressed through hand kissing and santri sambangan (visits) reflect respect, emotional connection, and community support. This symbolic interaction serves as character education for the students, instilling social ethics and cultural continuity. However, the focus of the study on one pesantren limits its generalizability. Future research should explore symbolic interactions in other pesantren to provide a broader perspective. The originality of this study lies in its focus on the role of symbols in shaping hierarchies and social identities in pesantren. By examining the pesantren educational environment, this study offers new insights into how symbols influence the dynamics of power, order, and communal values.